Automatic text summarization using fuzzy reasoning method - A., Alia; M., Nizam; N., Effendy; I., Fakhrul; A., Tanaka (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Automatic text summary (ATS) is a local-based applications developed to provide convenience to consumers who want the ease of everyday life. This system can simplify manual where it is able to generate a summary in a short time without changing the meaning of the original text. In particular, students and researchers who are doing research on a topic that requires them to read and review a document that has text length. Furthermore, this study will make a summary of the differences between the two types, namely, automated summary and summary produced by humans. It aims to look at how far can automatically match the summary report done by humans, which is a summary produced by trusted experts. MATLAB as a programming language to develop the system. Consequently, this study focuses on one of the subjects in Artificial Intelligence, which is fuzzy logic. The data used are from the Document Understanding Conference (DUC) 2002. Whereas for the purpose of valuation, the valuation metrics Recall-Oriented Evaluation Understudy for Gisting (ROUGE) has been used. Finally, the results will show one of the proposed method which has high performance.